Against COVID-19 vaccination of healthy children - Kraaijeveld, Steven R. (Bioethics, 2022)
COVID-19 vaccination of children has begun in a number of countries with provisional regulatory approval and public support. This article provides an ethical analysis of COVID-19 vaccination of healthy children. Specifically, we present three of the strongest arguments that might justify COVID-19 vaccination of children: (a) an argument from paternalism, (b) an argument from indirect protection and altruism, and (c) an argument from global eradication. We offer a series of objections to each of these arguments to show that none of them is currently tenable. Given the minimal direct benefit of COVID-19 vaccination for healthy children, the potential for rare risks to outweigh these benefits and to undermine vaccine confidence, the substantial evidence that COVID-19 vaccination confers adequate protection to risk groups whether or not healthy children are vaccinated and that current vaccines do not provide sterilizing immunity, and given that eradication of the virus is neither feasible nor a high priority for global health, we argue that routine COVID-19 vaccination of healthy children is currently ethically unjustified. Since mandates for children have already been implemented in some places (e.g., California) and may be considered elsewhere, we also present two additional arguments explicitly against making COVID-19 vaccination mandatory for children.